ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDUDUK MISKIN DAN UPAH MINIMUM TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN BUNGO 2014-2021 - Lina Marliana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Indicators of socio-economic development have long been a matter of debate. Economists and non-economic groups have challenged the question of per capita income as an indicator of development because of the inaccuracy of these indicators, so several new indicators have emerged. The new indicators generally focus on human development. This study aims to describe the influence of independent variables such as the number of poor people, economic growth and the minimum wage on the Human Development Index in Bungo. The research method used is multiple linear regression analysis and processed using the SPSS application. Based on the t-test, have been found that economic growth and workers' minimum wage had a significant effect on the Human Development Index. In contrast, the number of poor people had no significant effect on the Human Development Index. The regression model in this study is the Best Linear Unbiased Estimator (BLUE). This research is expected to be used as input for human development planning in Bungo Regency.